Bilateral superficial cervical plexus block as sole anesthesia for parathyroid surgeries in chronic kidney disease patients - Kanika Agarwal; Sharma, Nidhi; Sharma, Aseem; Banjare, Manish (Asian Journal of Medical Sciences, 2024)
Chronic kidney disease (CKD), especially in stages III, IV, V patients presenting for surgical removal of parathyroid glands, has special concerns regarding anesthesia. Their renal disease restricts the choice of drugs that can be used for general anesthesia induction and management. Bilateral superficial cervical plexus block (SCPB) under ultrasound guidance can be an alternative mode of anesthesia in parathyroid surgeries in these patients. The aim of the present case series was to evaluate the effectiveness of bilateral SCPB in CKD (stages III, IV, V) patients undergoing parathyroid surgeries in terms of hemodynamic stability, intraoperative and post-operative analgesia, and surgeon’s satisfaction. In the present case series, USG-guided bilateral SCPB was performed under aseptic precautions and 10 mL of local anesthetic was injected on each side. Effect was confirmed with wet swab and blunt pin prick. Then, patient was handed over to the surgeon. Continuous hemodynamic monitoring was done and time of first rescue analgesia was noted. Bilateral SCPB proved to be a good alternative mode of anesthesia for CKD (stages III, IV, V) patients undergoing parathyroid surgeries.